Genre fission : a new discourse practice for cultural studies - Barr, Marleen S. (University of Iowa Press, 2000)
What do Amsterdam prostitutes, NASA astronauts, cross-dressing texts, and Star Trek characters have in common? In Genre Fission, Marleen Barr wittily and eccentrically revitalizes cultural and literary theory by examining the points where such vastly different categories meet, converge, and reemerge as something new.